No immediate or future extra costs of raising a virulent brood parasite chick. (3rd April 2019) - Samaš, Peter; Grim, Tomáš; Jelínek, Václav; Abraham, Marek M; Šulc, Michal; Honza, Marcel
Abstract: Parental care is an adaptive behavior increasing the survival of a young. Virulent brood parasites, like the common cuckoo Cuculus canorus, avoid the parental care and leave the care for their nestlings to hosts. Although raising a cuckoo is always costly because it kills host's progeny, to date it is not known whether raising of a brood parasite itself represents any extra cost affecting host's fitness, that is, a cost above the baseline levels of care that are expended on raising the host own young anyway. We quantified costs of rearing a cuckoo nestling in the most frequent host, the reed warbler Acrocephalus scirpaceus . We measured changes in the host physical (body mass) and physiological conditions (stress levels quantified via heterophils/lymphocytes ratio) within the 1 breeding attempt (immediate cost) and retrapped some of these adults in the next breeding season to estimate return rates as a measure of their survival (future cost). In contrast to universal claims in the literature, raising a cuckoo nestling did not entail any extra immediate or future costs for hosts above natural costs of care for own offsprings. This counterintuitive result might partly reconcile theoretical expectations in the hosts with surprisingly low levels of counter-defences, including the reed warbler. Unexpectedly low raising costs of parasitism may also help explain a long-term maintenance of some host–parasite systems. Abstract : Raising a large brood parasite chick should be very costly to a small passerine host. By quantifying several cost parameters in the reed warbler host, we showed that rearing a parasitic cuckoo was not associated with an extra physical and physiological costs and did not affect host survival. No extra costs of raising a brood parasite chick might contribute to low levels of counter-defences in some hosts and a long-term maintenance of some host–parasite systems.